New accents in the organization of individual work of students - Kantserova, Maryna; Antraptseva, Nadia; Ponomareva, Iryna; Bila, Galina (My University, 2011)
Independent work among the various forms and methods of educational work is one of the main places its priority role to play in enhancing students' creative thinking, look for them a personal interest in the acquisition of knowledge and skills. Being one of the most difficult moments in the educational process, independent work time is the most effective form of training of future professionals. According to credit-module system capacity for independent research is a necessary component of the overall competence of students. Самостійна робота серед різних форм і методів виховної роботи займає одне з головних місць, її пріоритетна роль належить в активізації творчого мислення студентів, зовнішній вигляд для них особисту зацікавленість в придбанні знань і навичок. Будучи одним із найскладніших моментів в організації навчального процесу, самостійна робота одночасно є найбільш ефективною формою навчальної діяльності майбутніх фахівців. Відповідно до кредитно-модульної системи навчання потенціал для незалежних досліджень є необхідною складовою загальної компетентності студентів.
Keywords: іndependent work of students; credit-module system; самостійна робота студентів; кредитно-модульна система навчання; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів